Recovery and germinative response of Amaranthus deflexus L. seeds under different levels of water stress and luminosities - Fontes, Larissa de Oliveira; Oliveira, Alexandre Bosco de; Filho, Eneas Gomes; Lopes, Maria de Fátima de Queiroz; Costa Filho, José Hamilton da; Silva, Ítalo Nunes (Comunicata Scientiae, 2019)
The objective of this work was to evaluate, in two experiments, the effect of water stress and luminosity on the germinative behavior and vigor of Amaranthus deflexus L seeds. The seeds were sown in Petri dishes containing two sheets of filter paper moistened with distilled water, in the control treatment. Using this treatment-control configuration, as a standard of comparison, two assays were performed using subsamples from the same A. deflexus seed population. In the first experiment (experiment 1), solutions of polyethylene glycol 6000 (PEG 6000) were used, providing osmotic potentials of -0.3; -0.6; -0.9; -1.2 and -1.5 MPa; however, in the second trial (experiment 2) osmotic potentials of -0.1; -0.2; -0.3; -0.4 and -0.5 MPa were used. At the end of the test, the ungerminated seeds for each treatment were washed and germinated on a filter paper moistened with water. The germination and vigor of the seeds were evaluated through the first germination count, germination test, germination speed index and average germination time. The experimental design was completely randomized, in a 2 x 6 factorial scheme, totaling twelve treatments, with four replicates of 50 seeds each, in both trials. Water stress negatively affects the performance of A. deflexus seeds, reducing germination and vigor from -0.1 MPa. Seed germination was compromised by the absence of light, regardless of the applied stress levels. There was an increase in seed germination after application of the same at higher levels of water stress.